The Blood-Brain Barrier Choline Transporter - J. Geldenhuys, Werner; D. Allen, David (Central Nervous System Agents in Medicinal Chemistry, 2012)
Drug delivery to the brain is made difficult by the blood-brain barrier (BBB) which is selectively permeable to organic drug compounds. Several membrane solute and nutrient transporters are expressed in the BBB vasculature, which may be utilized as mechanism of delivery of drugs to the brain. Of interest to us, are the organic cation transporters which could be used to transport cationic compounds into the CNS. In this mini-review, we will review the current understanding of the structural requirements for designing compounds which could effectively use organic cation transporters (OCT). For the first time, structural requirements for both OCT1 and OCT2 versus the BBB choline transporter (BBBCHT) are discussed and compared. The information gained here could increase the success rate in successful CNS drug delivery and therapeutics.
Keywords: In situ brain perfusion